2018
DOI: 10.1080/1120009x.2018.1451030
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric HIV-1 infection: updated strategies of prevention mother-to-child transmission

Abstract: Data are accumulating on efficacy, effectiveness and safety of different PMTCT strategies in various possible clinical scenarios, however further researches are needed in order to optimize the management of infants at extremely low risk for MTCT as well as in those presenting with high risk for infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…All pregnant mothers should be screened for HIV in the first trimester: for infants born to mothers with unknown HIV status, a rapid HIV screening of mothers and/or infants should be performed as soon as possible, either during labor or after delivery, starting immediately the appropriate neonatal postexposure prophylaxis (PEP) if the test is positive [ 147 ].…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…All pregnant mothers should be screened for HIV in the first trimester: for infants born to mothers with unknown HIV status, a rapid HIV screening of mothers and/or infants should be performed as soon as possible, either during labor or after delivery, starting immediately the appropriate neonatal postexposure prophylaxis (PEP) if the test is positive [ 147 ].…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…Prevention of mother-to-child human immunodeficiency virus (HIV) transmission during pregnancy, delivery, and breastfeeding by using antiretroviral therapy (ART) has proven to be extremely beneficial in reducing the number of new HIV-1 infections in children. The antiretroviral (ARV) drug regimens used for pregnant women and neonates include nucleoside reverse transcriptase inhibitors (NRTIs), non-nucleoside reverse transcriptase inhibitors (NNRTIs), protease inhibitors (PIs), or integrase strand transcriptase inhibitors (INSTIs) with treatment frequency and duration dependent on the risk factors involved. , However, these treatments have their challenges with modulating metabolic pathways in both the mother and the newborn resulting in dyslipidemia, glucose intolerance, and abnormal mitochondrial function or adrenal dysfunction. The PI ritonavir-boosted lopinavir regimen, also known as Kaletra, is used during pregnancy or as a prophylactic treatment for neonates and has been associated with premature birth and transient adrenal insufficiency in newborns. , Previous studies have shown elevated plasma concentrations of adrenal steroid hormones including 17α-hydroxy progesterone (17-OHP), dehydroepiandrosterone (DHEA), and dehydroepiandrosterone 3-sulfate (DHEA-S) in neonates receiving the Kaletra treatment (Figure ). ,, Several hypotheses regarding the mechanism of adrenal hormonal imbalance and the associated life-threatening symptoms observed in newborns subjected to Kaletra therapy have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study conducted on HIV-exposed infants, Yitayew et al [30] reported that ARV drugs given to the mother during pregnancy and the administration of an ARV prophylaxis to the infant was the two most significant factors in avoiding perinatal HIV transmission. In a systematic review, Lumaca et al [31] reported that an optimal ART regimen and the use of intrapartum ZDV for pregnant women are recommended to reduce perinatal HIV transmission. One mother in this study who gave birth at another hospital received an intrapartum prophylaxis with IV ZDV.…”
Section: Discussionmentioning
confidence: 99%